Diseño del Restaurante y Cafetería de comidas típicas "ALMA LOJANA", mediante la elaboración del plan de negocios para promover el desarrollo del Turismo Gastronómico, en el Sur de la Ciudad de Quito, Cantón Quito, Provincia de Pichincha - Romero Torres, José Enrique (2018)
The city of Loja, known as the sentinel of the south, which contributes with cultural elements, which must be rescued, valued as for example their customs, traditions, music, dance, traditional gastronomy, are aspects that strengthen their identity of cultural wealth. . Within the typical Gastronomy are the cecina, dry goat, dry chicken, dry rib, repe, vetch with guineo, tamales, humitas, wadding, also their drinks such as horchata, coffee, among others, which is why the present study was carried out, whose main objective was to design the restaurant and cafeteria of typical foods "Alma Lojana", through the elaboration of the Business Plan to promote the development of gastronomic tourism, in the south of the city of Quito. , Quito canton, province of Pichincha, for which some methods were used such as synthetic, descriptive, inductive-deductive analytical and statistical analysis; likewise, some techniques, such as the bibliographic review and the survey, which allowed gathering the necessary information for the development of the investigation. Based on the collection of information, the analysis of the different studies was carried out, obtaining results in each of its stages. The financial evaluation produced the following results: the net present value that gave a value of $ 159,721, which means which is greater than the investment of $ .19,292; the Internal Rate of Return of 146.12% that is greater than the opportunity cost of 10%, the period of capital recovery that will be carried out in 3 years 10 months, the Benefit / Cost Ratio that yields a return of $ 0, 25 for each dollar invested, and the sensitivity analysis that supported an increase in costs of 15.30% and a decrease in revenues of 12.55, which means that the project is not sensitive therefore it is profitable.